1991
DOI: 10.1111/j.1365-2125.1991.tb03958.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies with abanoquil (UK‐52,046) a novel quinoline alpha 1‐ adrenoceptor antagonist: I. Effects on blood pressure, heart rate and pressor responsiveness in normotensive subjects.

Abstract: 1 Abanoquil (UK 52,046) is a novel, quinoline-derivative, oxl-adrenoceptor antagonist which, on the basis of animal studies, possesses antiarrhythmic activity at doses which have little or no effect on blood pressure. 2 In two placebo-controlled, double-blind, crossover studies the cX1-adrenoceptor antagonist activity (phenylephrine pressor responses) and the effects on blood pressure and heart rate (in the presence and absence of concomitant 13-adrencoeptor blockade) have been investigated in healthy, normote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…This study confirms and extends the results of previous studies with abanoquil (Schafers et al, 1991) with rightward shifts of the phenylephrine dose-responses, maximal at 1 h but detectable for up to 12 h after a single intravenous dose. The preliminary pharmacokinetic analysis suggests that the whole blood concentration-time profile of intravenous abanoquil is most appropriately described by a two-compartment model as has previously been found for both prazosin and doxazosin (Meredith et al, 1985), with a mean terminal elimination half-life of around 6 h. In the studies with prazosin and doxazosin the measured blood concentrations were around 10 ng ml-' i.e.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This study confirms and extends the results of previous studies with abanoquil (Schafers et al, 1991) with rightward shifts of the phenylephrine dose-responses, maximal at 1 h but detectable for up to 12 h after a single intravenous dose. The preliminary pharmacokinetic analysis suggests that the whole blood concentration-time profile of intravenous abanoquil is most appropriately described by a two-compartment model as has previously been found for both prazosin and doxazosin (Meredith et al, 1985), with a mean terminal elimination half-life of around 6 h. In the studies with prazosin and doxazosin the measured blood concentrations were around 10 ng ml-' i.e.…”
Section: Discussionsupporting
confidence: 91%
“…The results of preliminary studies in man have been consistent with those of animal studies in suggesting that abanoquil (UK-52,046) (4-amino-6-7-dimethoxy-2 -(1,2,3,4 -tetrahydro -6,7 -dimethoxyisoquinol -2 -yl) quinoline methanesulphonate) may have a relative selectivity for cardiac rather than peripheral vascular xl-adrenoceptors (Aubry et al, 1988;Schafers et al, 1991;Uprichard et al, 1988). Thus, although 'conven-tional' oxl-adrenoceptor antagonist drugs (e.g.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…In another study, 12 investigators used a higher dose of MK 0467 and found an increase in CI and Do 2 with no deleterious effects. In the present study, we chose not to evaluate administration of MK 0467 alone on the basis of results of other studies 4,12,16,17 and in recognition of the fact that the only anticipated clinical use of the receptor antagonist would be in conjunction with the α 2 -adrenoceptor agonist.…”
Section: Discussionmentioning
confidence: 99%
“…The classical method for analysis of receptor antagonism in vivo is the administration of increasing doses of agonist with measurement of shifts in the dose‐response curve in the presence of antagonist. For studies of α 1 ‐adrenoceptor antagonists this usually involves the agonist phenylephrine with measurements of DBP elevations as an indicator of arterial vasoconstriction [ 25–28]. When standard therapeutic doses of tamsulosin (0.4 mg) and terazosin (5 mg) were given to fasting, healthy subjects, the extent of inhibition of DBP responses at several time points was so pronounced, especially for terazosin, that shifts of the phenylephrine dose‐response curve could not formally be calculated.…”
Section: Discussionmentioning
confidence: 99%